PENENTUAN AREA LUAPAN KALI BABON AKIBAT KENAIKAN DEBIT AIR BERBASIS SISTEM INFORMASI GEOGRAFIS - Arnita Ikke Sari; Bambang Sudarsono; Bandi Sasmito; Harianto Harianto (Departement Teknik Geodesi Universitas Diponegoro, 2013)
Semarang city is one of the regions in Indonesia are vulnerable to flooding. This condition is getting worse by the land subsidence during the year to reach 0,7 – 11,2 cm / year. Water flooding which inundate along the Kali Babon Watershed have flooded the area around the river. Starting from Bendung Pucang Gading, Kali Babon Watershed experiencing siltation due to the slope of a gentle stream them more prone to sedimentation, thereby reducing the drainage capacity.This research uses open source software Hec RAS version 4.1.0. to analyze the profile of the river water level and produce flood inundation area with a certain depth of flood discharge plans with 5, 10 and 25 years.Results obtained from the distribution of the data processing occurs on the widest flood area Sriwulan village, district. Sayung, Kab. Demak approximately 247,965 hectares and a depth ranging from 0,00154448 to 4,5808 meters at discharge of 5-years plan; 249,598 hectares and a depth ranging from 0,00154781 to 10,1064 meters at discharge of 10-years plan , 482,180 hectares with depths ranging from 0,000581622 to 12,6956 meters at discharge of 25-years plan.Keywords : Flood, Kali Babon, Watershed and Hec RAS